(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The research includes the introduction of the research, its importance, the research problem, and the research objectives, which are the preparation of special units for individual self-learning using compound exercises in some offensive skills in basketball and their implementation and knowing the effect of special educational units in individual self-learning using compound exercises in some offensive skills in basketball. Statistically significant differences between the results of the pre-tests and the results of the post-tests for the experimental and control groups in some offensive basketball skills and in favor of the post-tests. The sample is the sixth primary grade students (60), as well as the tests used, the exploratory experiment, the scientific foundations, the pre-tests, the application of individual self-learning, and the post-tests. The use of individual self-learning has a positive effect on offensive skills in basketball. It was clear from the results that the overlap between the use of individual self-learning and compound exercises had a positive effect on offensive skills in basketball.Emphasis on the use of individual self-learning in the physical education lesson for all school stages to learn the basic skills of basketball.Keywords: individual self-learning, compound exercises, offensive skills.